Ultrastructure characteristic of the endocrine cells of prostate in poorly differentiated adenocarcinoma - Prokopyuk O.V.; Volkov K.S.; Kurik O.G. (Морфологія, 2008)
A research purpose was a ultrastructural study of prostatic APUD-system at poorly differentiated adenocarcinoma. The electron-microscopic investigation of the endocrine cells of prostate in 6 patients with poorly differentiated adenocarcinoma and fragments of 3 prostates without a tumour process (control group) was performed. Both the increase of the morphofunctional activity and presence of dystrophic changes of endocrine cells of prostate was found. At tumours, built from dark cells, APUD-cells are in less, contain less of endocrine granules, what in light-cell adenocarcinoma, where their amount is comparative anymore and in a cytoplasm them there is a far of secretory granules.